2016
DOI: 10.1128/aem.00757-16
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Polyhydroxybutyrate Synthesis in the Soil Bacterium Bradyrhizobium diazoefficiens

Abstract: Polyhydroxybutyrate (PHB) is a carbon and energy reserve polymer in various prokaryotic species. We determined that, when grown with mannitol as the sole carbon source, Bradyrhizobium diazoefficiens produces a homopolymer composed only of 3-hydroxybutyrate units (PHB). Conditions of oxygen limitation (such as microoxia, oxic stationary phase, and bacteroids inside legume nodules) were permissive for the synthesis of PHB, which was observed as cytoplasmic granules. To study the regulation of PHB synthesis, we g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 50 publications
3
59
1
1
Order By: Relevance
“…Structurally, PhaP1 Bd ‐PhaP4 Bd are predicted to be predominantly alpha‐helical but only PhaP4 Bd contains additionally a C‐terminal region very rich in alanine residues (13 out of 34 amino acids) (Yoshida et al ., ). Besides, they are all proposed to oligomerize (Quelas et al ., ).…”
Section: Bradyrhizobium Diazoefficienssupporting
confidence: 73%
See 2 more Smart Citations
“…Structurally, PhaP1 Bd ‐PhaP4 Bd are predicted to be predominantly alpha‐helical but only PhaP4 Bd contains additionally a C‐terminal region very rich in alanine residues (13 out of 34 amino acids) (Yoshida et al ., ). Besides, they are all proposed to oligomerize (Quelas et al ., ).…”
Section: Bradyrhizobium Diazoefficienssupporting
confidence: 73%
“…Transcription of phaP 3 seems to be low and constant during growth, suggesting that this phasin does not have a relevant role in PHA metabolism (Yoshida et al ., ). On the other hand, the study of single and double mutants has revealed that the combined role of PhaP1 Bd and PhaP4 Bd must be crucial in determining the number and size of the granules (Quelas et al ., ).…”
Section: Bradyrhizobium Diazoefficiensmentioning
confidence: 97%
See 1 more Smart Citation
“…In Rhizobium etli, which is a symbiotic bacterium of plants, the ΔaniA (same as ΔphaR) mutant accumulated only 40% of polyhydroxybutyrate (PHB) compared to the wild-type strain by disappearance of PhaB protein expression (30). Also, in the case of the soil bacterium Bradyrhizobium diazoefficiens, when the phaR gene was knocked out, the expression of phaC2 became uncontrolled, and this led to rapid inhibition of PHB synthesis (32). Thus, PhaR is important to PHA biosynthesis, and it seems reasonable that the PHA synthetic mechanism has been primarily selected for survival at the free-living stage of the Burkholderia symbiont and secondarily coopted for survival under the symbiotic condition within the host insect (25).…”
Section: Resultsmentioning
confidence: 99%
“…PhaR is also identified as a negative regulator of PhaP in Paracoccus denitrificans (27). Also, PhaR was reported to control PHA synthesis in Rhizobia species (30)(31)(32). Although one phaP gene was characterized in our previous study (25), the functions of four other phaP family genes and one phaR gene have not been determined in the Burkholderia genome.…”
mentioning
confidence: 93%